Bright, dark optical and other solitons to the generalized higher-order NLSE in optical fibers - Baskonus, Haci Mehmet; Sulaiman, Tukur Abdulkadir; Bulut, Hasan (Springer, 2018)
In this paper, we study the generalized higher-order nonlinear Schrodinger equation analytically. We use two integral schemes for conducting this study. Dark, bright, combined dark-bright optical, singular soliton, soliton-like and trigonometric function solutions are successfully constructed. We give the constraint conditions for the existence of valid solutions. The 2D, 3D and the contour graphs for the dark and bright solitons are plotted.
Keywords: The sinh-Gordon equation; Optical fibers; Optical soliton